2006
DOI: 10.1016/j.neuron.2006.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Specific Phosphorylation of MeCP2 Regulates Activity-Dependent Bdnf Transcription, Dendritic Growth, and Spine Maturation

Abstract: Mutations or duplications in MECP2 cause Rett and Rett-like syndromes, neurodevelopmental disorders characterized by mental retardation, motor dysfunction, and autistic behaviors. MeCP2 is expressed in many mammalian tissues and functions as a global repressor of transcription; however, the molecular mechanisms by which MeCP2 dysfunction leads to the neural-specific phenotypes of RTT remain poorly understood. Here, we show that neuronal activity and subsequent calcium influx trigger the de novo phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

52
829
7
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 762 publications
(896 citation statements)
references
References 53 publications
(55 reference statements)
52
829
7
5
Order By: Relevance
“…44 On the other hand, BDNF promoter IV binds the transcriptional repressor, MeCP2 (a methyl-CpG-binding domain protein), in complex with the corepressor sin3a and HDACs. [45][46][47] Inhibition of HDAC by VPA or other inhibitors could cause dissociation of the repressor-corepressor complex from the promoter, resulting in transcriptional disinhibition. It is noteworthy that the antidepressant effect of imipramine is largely reversed by HDAC5 overexpression in the hippocampus of mice subjected to chronic defeat stress, which per se induces downregulation of BDNF III and IV mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…44 On the other hand, BDNF promoter IV binds the transcriptional repressor, MeCP2 (a methyl-CpG-binding domain protein), in complex with the corepressor sin3a and HDACs. [45][46][47] Inhibition of HDAC by VPA or other inhibitors could cause dissociation of the repressor-corepressor complex from the promoter, resulting in transcriptional disinhibition. It is noteworthy that the antidepressant effect of imipramine is largely reversed by HDAC5 overexpression in the hippocampus of mice subjected to chronic defeat stress, which per se induces downregulation of BDNF III and IV mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…345 There are also reports that Mecp2 plays a role in the regulation of Bdnf levels. 134,201,202 Reduction in the levels of Bdnf exacerbates the phenotype of both the Rett syndrome-model mouse 346 and the Sert deletion line. [208][209][210] In the Rett syndrome-model mouse, Bdnf overexpression with an inducible Bdnf transgene leads to partial correction of abnormalities linked to loss of Mecp2 function.…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that Mecp2 regulation of dendritic patterning and other components of neuronal connectivity is dependent on phosphorylation induced by neuronal activation. 134 The application of a selective CaMKII inhibitor, but not inhibitors of other kinases (CaMKK, protein kinase A, protein kinase C, mitogen-activated protein kinase, cyclin-dependent kinase 5 (CDK5), or phosphatidylinositol 3-kinase (PI3K)), blocked the stimulation-dependent phosphorylation of Mecp2, suggesting that CaMKII modulates the state of Mecp2 activation during synaptic transmission. 134 In addition to altered translation, dysregulation of CaMKII could occur through processes involved in autophosphorylation.…”
Section: Mouse Models Of Genetic Clinical Disorders With Autism Symptmentioning
confidence: 99%
See 2 more Smart Citations